Kemampuan Belajar Mandiri dan Kemampuan Literasi Baru Calon Guru Biologi - Dian Samitra; Fitria Lestari; Rambat Nur Sasongko; Muhammad Kristiawan (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the ability of self-regulated learning, new literacy and the relationship between the two in perspective biology teachers. The method used is qualitative. The research sample is Biology students, at PGRI Silampari University, totaling 74 people. The data collection instrument was in the form of a questionnaire consisting of self-regulated learning abilities and new literacy skills. The data obtained were analyzed descriptively and the relationship between the two was analyzed using Rank Spearman analysis. The results showed that the ability of prospective biology teacher students in self-study regulation was categorized as good, new literacy was sufficient and the relationship between the two obtained a significance value of 0.00 (<0.05). In conclusion, there is a relationship between the ability to regulate self-study and the new literacy ability of prospective biology teachers. Keywords: Prospective Biology Teacher, New Literacy, Self-Study Regulation